Cash Flows of the Enterprise: The Essence and Methods of Their Evaluation - Eshonqulov Akmal Qudratovich (International Journal on Integrated Education, 2022)
At any point in time, a firm can be viewed as a collection of capital coming from various sources: from investors, creditors, as well as income received as a result of the firm's activities. These funds are used for various purposes: the acquisition of fixed assets, the creation of inventories, the formation of receivables, and others. The article discusses theoretical approaches to the analysis of cash flow, compares the formation of indicators by direct and indirect method, examines the directions of cash flow, and explains the essence of cash flows and methods of their assessment.